Evaluation and Management of Traumatic Rectal Injury - Clark, Nina M.; Maine, Rebecca G. (Clinics in Colon and Rectal Surgery, 2023)
Traumatic injury to the rectum is rare but associated with high morbidity and mortality. In recent years, diagnostic and treatment recommendations for these complex injuries have changed. While rare, it is critical for general surgeons to understand the basic principles of injury assessment, damage control, and definitive management of traumatic rectal injuries. This article reviews the literature regarding the evaluation and management of traumatic rectal injuries.
Keywords: trauma; rectum; pelvic injury